Political decision-making in the Portuguese New State (1933-39): The dictator, the council of ministers and the inner-circle - Raimundo, Filipa (2019)
This article seeks to contribute to the study of political centralisation in Portugal under Salazar; focusing on the council of ministers and its decision-making role and exploring the links between the dictator and his ministers (1933-39). The authors discuss the centralist strategy of the dictator based on a quantitative and qualitative study of Antonio de Oliveira Salazar's diaries: detailed accounts of his routines, audiences, meetings and even telephone calls. Our conclusions indicate Salazar perceived his cabinet more as a crisis management committee, as meetings occurred irregularly and the agenda was considerably focused on internal and external crises and major international political events. The article also provides a more accurate notion of the main features of decision-making during the regime's institutionalisation by exploring Salazar's individual relations with his ministers and inner circle. As Salazarism is often compared to its Iberian counterpart, Francoism. important differences between the two regimes in this domain are noted.